2021
DOI: 10.1007/s40520-021-01873-4
|View full text |Cite
|
Sign up to set email alerts
|

A review on the COVID-19-related psychological impact on older adults: vulnerable or not?

Abstract: Background COVID-19 is a novel event of the twenty-first century. Therefore, contemporary research is required to determine the current pandemic's psychological impact on older populations. Soon after the COVID-19 outbreak, several narrative reviews and guidelines were released to support older adult's psychological wellbeing. However, a lack of data from original studies was reported until May 2020. Aim To identify studies published from May 2020 until January 2021 that quantitatively assessed the mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 64 publications
2
57
1
3
Order By: Relevance
“…Throughout both the first and second waves of the pandemic, older adults were more likely to present with anxiety/depression related concerns in a visit with their family physician than they were before the pandemic. This contrasts with other findings that suggest that older adults were more emotionally resilient in coping with the pandemic relative to younger age groups ( Klaiber et al, 2021 ; Parlapani et al, 2021 ). It is unclear whether the increased incidence of anxiety/depression related visits among older adults should be interpreted as an increase in the number of patients with depression or anxiety disorders.…”
Section: Discussioncontrasting
confidence: 99%
“…Throughout both the first and second waves of the pandemic, older adults were more likely to present with anxiety/depression related concerns in a visit with their family physician than they were before the pandemic. This contrasts with other findings that suggest that older adults were more emotionally resilient in coping with the pandemic relative to younger age groups ( Klaiber et al, 2021 ; Parlapani et al, 2021 ). It is unclear whether the increased incidence of anxiety/depression related visits among older adults should be interpreted as an increase in the number of patients with depression or anxiety disorders.…”
Section: Discussioncontrasting
confidence: 99%
“…Multivariate logistic regression revealed protective factors in age>35, the malesex, higher educational level, night sleep hours >7, and being physically active. Regarding the role of age, previous evidence revealed controversial results ( Parlapani et al, 2021 ), with some studies showing old age as a risk factor for peritraumatic distress ( Qiu et al, 2020 ; Shrestha et al, 2020 ), while other studies identified it as a protective factor ( Al-Hanawi et al, 2020 ; Costantini and Mazzotti, 2020 ; Gloster et al, 2020 ; Jiménez et al, 2021 ; Ramasubramanian et al, 2020 ), or did not find any significant association with age ( Megalakaki et al, 2021 ). A possible explanation for the decrease in the risk of peritraumatic distress with advancing age could be the greater knowledge of the older population with respect to epidemic events.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there are some recent evidence from Austria or Germany suggesting that loneliness was not increased during the COVID-19 outbreak ( 34 36 ). According to a recent review, the adaptive ability of older people in the face of COVID-19 may vary based on social, cultural, and economic factors ( 37 ). In a study in German and Polish populations during the COVID-19 pandemic, older people were found to have a higher level of quality of life, wellbeing, and life satisfaction and a lower level of anxiety.…”
Section: Discussionmentioning
confidence: 99%